Teachers' Creativity in Science Education Through Play-Based Learning to Foster Students' Naturalist Intelligence - Prety Febriyanti; Abdussahid Abdussahid; Syahru Ramadhan (Journal of Education and Teacher Training Innovation, 2026)
This study was motivated by the low level of student engagement and the suboptimal development of naturalistic intelligence in science education in elementary schools, which is still dominated by conventional methods. This study aims to describe the creativity of teachers in implementing game-based learning methods as an effort to foster students' naturalistic intelligence at SDN Kamunti. This study used a qualitative approach with a descriptive research design. Data sources included teachers, principals, and students, as well as relevant learning documents. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis techniques involved the stages of data reduction, data presentation, and drawing conclusions. The results showed that teachers creatively developed learning through game-based activities, such as environmental exploration, mini-experiments, outdoor exploration games, the use of recycled materials, and role-playing based on local projects. Observational data showed that students actively observed, classified, and interacted directly with natural objects. Interview results revealed that teachers deliberately designed lessons so that students could learn through games and direct experiences. Field notes confirmed the findings that students showed high enthusiasm, collaborated in groups, and were able to explain their observations in their own words. Thus, the implementation of play-based learning has been proven effective in creating meaningful learning experiences, increasing student engagement, and optimally fostering naturalistic intelligence.